2017
DOI: 10.1093/jee/tox244
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Culex quinquefasciatus (Diptera: Culicidae) in Southern Louisiana to Larval Insecticides

Abstract: Mosquito control districts conduct rigorous insecticide treatments against both larval and adult Culex quinquefasciatus Say (Diptera: Culicidae), the primary vector of West Nile virus in the southern United States. However, the development of resistant populations of Cx. quinquefasciatus in response to extensive larvicide or adulticide applications has been demonstrated repeatedly across the world. Examining changes in insecticide susceptibility in treated field areas can help inform mosquito control districts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Given the recent spread of West Nile virus across the continental United States, the existing global disease burden of lymphatic filariasis [3], as well as reported resistance to existing larvicides [48], it is also useful that syt.427 has larvicidal activity in C . quinquefasciatus (Fig 6C).…”
Section: Resultsmentioning
confidence: 99%
“…Given the recent spread of West Nile virus across the continental United States, the existing global disease burden of lymphatic filariasis [3], as well as reported resistance to existing larvicides [48], it is also useful that syt.427 has larvicidal activity in C . quinquefasciatus (Fig 6C).…”
Section: Resultsmentioning
confidence: 99%
“…As a member of a new class of larvicides, sema.460 could help combat resistance to existing insecticides, an ever-growing problem [10–16, 52]. Moreover, through our efforts to build an arsenal of interfering RNA larvicides ([25, 26], this study), we are working to combat resistance that could potentially develop due to a mutation in any one shRNA target site.…”
Section: Discussionmentioning
confidence: 99%
“…4c). The existing global disease burden of lymphatic filariasis [3], recent spread of West Nile virus across the continental United States, and reported resistance to existing larvicides [52] make the development of new larvicides for control of Culex pipiens complex mosquitoes a vital necessity. Larvicides for control of Culex mosquitoes are often used to treat stormwater catch basins, which are known to be important breeding sites for Culex mosquitoes in urban and suburban regions [6062].…”
Section: Discussionmentioning
confidence: 99%
“…This study correlates with previous studies that only used the larval stage of Cx.quinquefasciatus. For example, DeLisi et al [35] in East Baton Parish, Louisiana, only used Cx.quinquefasciatus larvae to assess the susceptibility of Cx.quinquefasciatus to larval insecticides (Lysinibacillus sphaericus, spinosad, and temephos). DeLisi's research results found that Cx.…”
Section: Discussionmentioning
confidence: 99%